Implementasi Reforma Agraria Terhadap Pemenuhan Harapan Masyarakat Yang Bersengketa Lahan - Sri Martini; Maiza Hazrina Ash-Shafikh; Nur Choirul Afif (BHUMI: Jurnal Agraria dan Pertanahan, 2019)
Abstract: Agrarian reform policy in Indonesia has become a very important issue. Indonesia has tried to carry out agrarian reform by making various changes in laws and government policies. This is a descriptive research aiming to describe the phenomena occurring in the field as well as a verification research aiming to examine the effect of the implementation of agrarian reform on the positive response of affected community in Punggelan Village, Punggelan Subdistrict, Banjarnegara Regency, Central Java Province. The type of research is explanatory research that aims to explain the effect of the variable of agrarian reform strategy implementation on the response of the affected community. The data in this study was collected through distribution of 100 questionnaires to the affected community and interviews with officials from the National Land Agency office, the Chairperson of the farmers’ group, and the farmers working on disputed lands. The results showed that there was a positive and significant influence of agrarian reform on the response of the affected community. This means that agrarian reform was able to meet the needs and expectations of the affected community. Intisari: Kebijakan reforma agraria di Indonesia menjadi isu yang sangat penting. Indonesia sudah berusaha melakukan reforma agraria dengan melakukan berbagai perubahan perundang-undangan dan kebijakan pemerintah. Penelitian deskriptif ini bertujuan untuk menggambarkan fenomena yang terjadi di lapangan dan verifikatif bertujuan untuk menguji pengaruh implementasi reforma agraria terhadap responss positif masyarakat terdampak di Desa Punggelan, Kecamatan Punggelan, Banjarnegara–Jawa Tengah. Jenis Penelitian ini merupakan penelitian eksplanatori yang bertujuan menjelaskan pengaruh variabel implementasi strategi reforma agraria terhadap respons masyarakat terdampak. Pengumpulan data pada penelitian ini melalui penyebaran 100 kuesioner terhadap masyarakat terdampak dan wawancara kepada pejabat kantor Badan Pertanahan Nasional, Ketua Kelompok petani dan petani penggarap lahan sengketa. Hasil penelitian menunjukkan bahwa terdapat pengaruh positif dan signifikan reforma agraria terhadap respons masyarakat terdampak. Artinya reforma agraria mampu memenuhi kebutuhan dan mendapatkan respons positif dari masyarakat yang bersengketa lahan.